Reading Motivation: Classroom-Based Instruction and Technology Support - Ling Li; Antoinette Doyle (Canadian Society for Studies in Education, 2020)
This paper aims to provide an overview of the reading motivation enhancing strategies that teachers can use in their classrooms based on a review of previous research. At first, effective classroom practices, such as making reading relevant, offering choices, providing proximal challenges, collaborative learning, using extrinsic incentives, are reviewed along with their theoretical and empirical rationales. Second, the newly arising electronic-text reading was specially concerned with an emphasis on its potential to promote children's reading motivation. It was revealed that electronic-text reading based on new technologies seems to have positive effects on children's reading motivation. Yet,  this type of reading also has a risk of distracting children, and its effects are also challenged by some researchers and required more research to examine further in the future. Thus, teachers should be cautious enough when using electronic-text reading to promote children's reading motivation in their classrooms.